The Influence of Parental Mediation to Perception of Television Negative Effect On Childrens - Awita Setyaningrum .; Drs. Hj. Sri Widowati H., MS (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Watching television still being one habits child who can give the effect of negative to the progress starting from increase the nature of passive to increase of knowledge and experience sexual in a premature manner. Although, the child gets actively for watching television a pertaining to programs even the impact of watching television, but children still need their parents to help well understand about it. Parental mediation when watching television is one of strategy used parents to reducing the negative impact of television and children's perception of the television. As an agent on the first, the parents have an important role in a period of growth children. One of which is in the formation of perception. This research aims to understand the influence of parental mediation against perception the negative effects of television on children. To answer these problems used parental mediation theory. This type of research is explanatory research. The population in this research was children aged 10 to 12 years in the city of Semarang is within 1 month of the last television in parental mediation, either actively, restrictive and co-viewing mediation. Respondents who taken are number of 120 respondents using non-probability techniques sampling. The first hypothesis test results in this study indicate that the variable restrictive mediation (X1) does not significantly affect the perception variable negative effect on children's television (Y), while the significance of the results shows the value of 0.523. The second hypothesis test showed that the active mediation variables (X2) did not significantly influence the perception variable negative effect on children's television (Y), with the results showing the significance value of 0.274. And the third hypothesis test shows that coviewing mediation variable (X3) does not significantly influential the perception of television positive effect on children (Y), with the results indicated the value of 0.184.